EFEKTIVITAS PUPUK HAYATI DAN PUPUK NITROGEN (ZA) DALAM MENINGKATKAN HASIL DAN MUTU TEMBAKAU VIRGINIA SERTA POPULASI BAKTERI DAN KADAR N TOTAL TANAH - DJAJADI DJAJADI; A. S. MURDIYATI; TITIEK YULIANTI; HERI ISTIONO (Pusat Penelitian dan Pengembangan Perkebunan, 2000)
Effectiveness of biofertilizer and IS fertilizer (ZA) in increasing the yield and quality of Virginia tobacco leaves, population of soil bacteria and soil /V contentThe experiment was conducted in inceptisol soil, Bondowoso, from June 1998 to March 1999. The experiment was aimed to study the effect of biofertilizer and N rates on population of soil bacteria and total N soil content, yield and quality of Virginia tobacco leaves The experiment was designed in factorial randomized block with two factors and four replicates Factor one consisted of two levels of biofertilizer (0 and I l/ha) and factor two was three levels of N rates (0, 25 and 50 kg N/ha). Biofertilizer was sprayed before planting and N fertilizer was added twice, at 10 and 21 days ater planting, half dosage each PjO^ (40 kg/ha) and K20 (90 kg/ha) were added as basal fertilizer. Biofertilizer (1% product) was sprayed into the plant holes (volume 100 l/ha) prior lo planting of tobacco seedlings. Results showed that interaction between biofertilizer and 2S kg N/ha treatments increased fresh leaves yield by 22% and cured leaves by 30%, and also resulted in a high value of crop index (110.16) Quality index was only increased (5%) by addition of biofertilizer In the laboratory, the combination treatment of biofertilizer and N also increased the population of bacteria and total N content of soil that was incubated for 2 weeks.